Issues and trends of portfolio diversification - Shari, Aminah; Mahat, Fauziah; Dahir, Ahmed Mohamed (Human Resource Management Academic Research Society, 2019)
The concept of diversification has been a great importance in risk management and investment decision making in the capital market. The purpose of this paper is to examine the issues and trends of diversification of risk on capital market. In addition, the paper highlight some of the latest trends and developments in the area namely multi-asset class investment and co-movement of risk and return. Moreover, in light of the basis of modern capital market theory developed by Harry Markowitz, the paper review some of the approaches developed to address the challenges encountered when using diversification strategy in practice, including the portfolio choice problem, alternative assets class and time-varying volatility assessment.